Employing English in the workplace for communication and interaction - Tutuk Widowati (UPT P2M Politeknik Negeri Malang, 2012)
The EFL teaching in Indonesia has been considered as a failure as proven by the fact that senior high school graduates cannot use it in the society. Studies conducted to improve students speaking skill seem to miss the importance of language inputs. Therefore, in this article the writer tries to give ideas on how to design and English teaching materials for workplace/workshop English class for Civil Engineering students following Hutchinson and Waters (1987:108). With such a model, a lesson (material) consists of four elements: input, content focus, language focus, task. Inside this model, there is a vocabulary building part. And to be comprehensive, the tasks consist of language task, writing task, and speaking task.